2016
DOI: 10.3389/fnins.2016.00275
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Controller on an FPGA Applied to Closed-Loop Diaphragmatic Stimulation

Abstract: Cervical spinal cord injury can disrupt connections between the brain respiratory network and the respiratory muscles which can lead to partial or complete loss of ventilatory control and require ventilatory assistance. Unlike current open-loop technology, a closed-loop diaphragmatic pacing system could overcome the drawbacks of manual titration as well as respond to changing ventilation requirements. We present an original bio-inspired assistive technology for real-time ventilation assistance, implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our architecture demonstrated its accuracy in real-time, long-term [ 4 , 21 , 33 , 34 , 35 , 39 ] experiments. Furthermore, current FPGA use is below its maximum processing potential, as only a few electrodes and simple feedback rules have been exploited.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our architecture demonstrated its accuracy in real-time, long-term [ 4 , 21 , 33 , 34 , 35 , 39 ] experiments. Furthermore, current FPGA use is below its maximum processing potential, as only a few electrodes and simple feedback rules have been exploited.…”
Section: Discussionmentioning
confidence: 89%
“…In this experiment, no stimulation artifact was observed as no stimulation was actually performed on the culture. Closed-loop experiments using Multimed were recently performed in two research projects: the BRAINBOW project [ 33 ], exploring functional organization and the dynamics of damaged parts of the central nervous system, and the CENAVEX project [ 34 , 35 ], which implements a real-time control scheme for ventilation after spinal cord injury impairing respiratory functions.…”
Section: Existing Applicationsmentioning
confidence: 99%
“…Previous studies have suggested technology that can be used to synchronize artificial ventilation with intrinsic respiratory drive or to replicate its function. These methods include development of a controllable stimulator with an update frequency higher than the stimulation frequency and a real-time processing controller (Castelli et al, 2017), implementation of a bio-inspired spiking neural network model that follows intrinsic respiratory rate (Zbrzeski et al, 2016), predictive algorithms using body temperature and heart rate (Kimura et al, 1992), and breath-triggering through the use of genioglossus muscle activity (Mercier et al, 2017). However, these approaches have not yet been sufficiently developed or investigated.…”
Section: Controller Provided Autonomous and Individualized Ventilatormentioning
confidence: 99%
“…They mainly rely on the development and implementation of a spiking neuron model and synapses that replicate the dynamics of neurons as close to real biological neurons as possible that fits in computational hardware. Two main directions of these studies are the use of analog computing simulating the network with specially designed VLSI integrated circuits (Indiveri et al, 2006;Silver et al, 2007) and numerical simulation of the model with specially designed microchips, GPUs FPGAs or DSPs (Yavuz et al, 2016;Zbrzeski et al, 2016;Cheung et al, 2016;Brette et al, 2007 and references therein). This paper focuses on the design, implementation and validation of a neuronal model that could be used in real-time simulations of relatively large networks using off-the-shelf 32-bit microprocessors.…”
Section: Introductionmentioning
confidence: 99%